IX Vneocherednoi s"ezd narodnykh deputatov Rossiiskoi Federatsii . IX Vneocherednoi s"ezd narodnykh deputatov Rossiiskoi Federatsii . 9th Extraordinary Congress of People's Deputies of the Russian Federation . IX Внеочередной съезд народных депутатов Российской Федерации - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Congress convenes following a televised address by President Boris Yeltsin in which he declared assumption of "extra-ordinary powers"; Congress attempted to dismiss Yeltsin from the office of President. Simultaneous vote on the resignation of the chairman of the Supreme Soviet, Ruslan Khasbulatov. Featured in the program: Yeltsin, Boris Nikolayevich (President of the Russian Federation); Tarasov, Boris (People's Deputy); Volkogonov, Dmitrii Antonovich (Advisor to the President of Russia on Defense Issues); Stepanov, Viktor (People's Deputy); Stepankov, Valentin Georgievich (Chief State Prosecutor of the Russian Federation); Solodiakova, Nina (People's Deputy); Shuikov, Valerii (People's Deputy); Verenchuk, Viktor (People's Deputy); Sorokina, Mariia (People's Deputy); Kazarov, Oleg (People's Deputy); Egorov, Vladimir (People's Deputy); Tikhonov, Vladimir Aleksandrovich (People's Deputy); Kadmenskii, Stanislav (People's Deputy); Zakharov, Andrei (People's Deputy); Saenko, Gennadii (People's Deputy); Skokov, IUrii (Secretary of the Russian Security Council); Vil'chek, Mikhail (People's Deputy); Andronov, Iona Ionovich (People's Deputy) Съезд созван в связи с телеобращением Президента Бориса Ельцина, в котором он объявил о введении "особого порядка управления" страной. Съезд предпринял попытку отстранения Бориса. Ельцина от должности Президента. Одновременно состоялось голосование об отставке председателя Верховного Совета Руслана Хасбулатова. В программе участвуют: Ельцин, Борис Николаевич (Президент Российской Федерации); Тарасов, Борис (Народный депутат); Волкогонов, Дмитрий Антонович (Советник президента России по оборонным вопросам); Степанов, Виктор (Народный депутат); Степанков, Валентин Георгиевич (Генеральный прокурор Российской Федерации); Солодякова, Нина (Народный депутат); Шуйков, Валерий (Народный депутат); Веренчук, Виктор (Народный депутат); Сорокина, Мария (Народный депутат); Казаров, Олег (Народный депутат); Егоров, Владимир (Народный депутат); Тихонов, Владимир Александрович (Народный депутат); Кадменс